PERAN KEPALA KUA DALAM MENANGANI NIKAH SIRI DI DESA JUNREJO KOTA BATU - Muhammad Ihsan Fathoni; Ibnu Jazari; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Marriage is an inner and outer bond between a man and a woman to live an orderly family life together. In Islamic law, a marriage is considered valid, that is, if it has fully fulfilled the pillars and conditions of marriage regulated in Islamic law. According to Article 1 of the 1974 Marriage Law, it is obligatory for people to have legitimate children and families in order to live happily in this world and the hereafter, under the auspices of God's love and joy. As stated in Article 1 of the Basic Marriage Law Number 1 of 1974 which states that